Konsep Pendidikan Akhlak Dalam Islam - ZA, Zulida (Jurnal Dewantara, 2017)
Moral education is an education system that can give a person the ability to lead a life with Islamic ideals, the values of Islam has been animating and coloring style personality. So morality is a behavior that has been inherent in a person due to the habit of doing so yeah do spontaneously. Good and bad human behavior referred to as moral decency which means life principle or regulation norms. Moral concept is not only studied in theory but to encourage people to do the will, so as to form a holy life and produces perfect goodness. Morals are a reflection rather than Muslims who must have basic. This is what must be lived and practiced so that the creation of a noble character.